Plant biotechnologies in Senegal - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
A new plant biotechnology laboratory opened in Dakar, Senegal, in October 1991. It was funded by the French Ministry for Cooperation and was set up by the Senegal Institute for Agricultural Research (ISRA) and the institut francais de recherche...